Korupsi Dalam Ranah Demokrasi di Indonesia - Said Zainal Abidin (Puslatbang KHAN, 2018)
The performance of democratization system in Indonesia was surrounded long time ago since 1959. Nevertheless, the corruption eradication in Indonesia must be performed few generation later. The democratization system in Indonesia has proven that it could not reduce the num ber and the amount of corruption. Ironically, the corruption is done by government apparatus that were selected by Indonesian people and it is also done by the legislative members at state level that function to supervise the government tasks on behalf of Indonesian people. Why the democratization system in Indonesia could not reduce the corruption? How to solve it in the future? This paper focuses on the obstacles of corruption eradication in Indonesia and offerssignificantsolutionsincomprehensiveways.